2012
DOI: 10.1002/app.36907
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the properties of plasma‐modified ground tire rubber‐filled cement paste

Abstract: The thesis investigated that the adhesion of ground tire rubber (GTR) to cement can be improved by applying surface plasma modification. The hydrophobic surface of GTR powder has been transformed to a hydrophilic one through plasma treatment. Attenuated total reflectance Fourier transform infrared spectral studies showed the increase in peak intensity at the range of 1400-1600 cm À1 , indicating the generation of carbon-carbon double bond after plasma treatment on the surface of the GTR powder. The X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 20 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Another important application area are composites. In this case, plasma‐treated polymer powders are used in fiber‐reinforced composites (e.g., carbon or sisal fibers) or as additives and tribological fillers with improved adhesion properties in high performance polymers or cement pastes . Another interesting application is the adhesion of sintered plasma‐modified PE powder on PUR foam products for the production of seats in the automotive industry or better isolated thermoboxes, i.e., for food industry…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important application area are composites. In this case, plasma‐treated polymer powders are used in fiber‐reinforced composites (e.g., carbon or sisal fibers) or as additives and tribological fillers with improved adhesion properties in high performance polymers or cement pastes . Another interesting application is the adhesion of sintered plasma‐modified PE powder on PUR foam products for the production of seats in the automotive industry or better isolated thermoboxes, i.e., for food industry…”
Section: Applicationsmentioning
confidence: 99%
“…Several researchers investigated the combination of a cold remote MW plasma afterglow with FBRs . Figure (I–L) shows used setups.…”
Section: Studies On Low‐pressure Plasma Reactorsmentioning
confidence: 99%
“…Moreover, there are some physical methods and chemical approaches used to modify the GTR. Some chemical methods such as the surface modification, oxidation or chlorination of GTR particles' surface are necessary in order to obtain a good adhesion with the polymer matrix and GTR powders and then improve mechanical properties of the blends according to literatures . Another possible method for compatibilization is the surface treatment of GTR particles using various physical methods such as like UV, electron‐beam, gamma ray etc.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Guo [4] showed that the filling effect of rubber particles effectively increases the elastic deformation ability of oil well cement stone through research on the effect of rubber powder in oil well cement. Cheng et al [5,6] and Long et al [7] modified rubber powder using low-temperature plasma technology and added modified rubber powder to the oil well cement. e elastic modulus of cement stone containing rubber particles is lower than that of pure cement, which can improve the plasticity and elastic deformation capacity of cement stone and make the structure of cement paste more compact.…”
Section: Introductionmentioning
confidence: 99%